Adaptive estimation of the hydraulic gradient for the location of multiple leaks in pipelines. (February 2020) - Rojas, J.; Verde, C.
Abstract: A scheme is proposed for detecting and locating multiple sequential leaks, based on a combination of an adaptive observer to identify the hydraulic gradient in real time and a leak location observer to estimate the leak position and its outflow. The main contribution is the use of an equivalent leak model which switches with an identification function for the hydraulic gradient without input excitation. Experimental results of a pilot pipeline showed a satisfactory estimation in spite of operation changes and leaks. Moreover they revealed that if leaks must be located, a precise knowledge of the hydraulic gradient is required. Highlights: Hydraulic gradient identification without input excitation of the system. Properties of the input output equivalent model for multiple leaks diagnosis. Minimal order observers for multileaks by a switched observer scheme.